THE IMPACT OF THE EXTENDED EXTERNAL AUDITOR'S REPORT ON THE RELEVANCE OF ACCOUNTING INFORMATION AND THE QUALITY OF EXTERNAL AUDITING: AN APPLIED STUDY - Merhej, Basim Mohammed (Journal of Economic and Economic Policy, 2026)
Objective: The purpose of this analysis was to establish the connection between the use of the extended audit report, as an independent variable, and the attainment of the relevance of accounting information and improvement of the quality of external auditing, as the last two variables are referred to as dependent. The analysis of this relationship was done by studying the extended audit report, with the main aim of identifying the significant developments that have taken place in such reports under the backdrop of the recent professional publications. The paper has also determined the key qualitative features that have been included in the accounting information to enable it be better placed to serve the needs of the users in terms of quality and disclosure. Besides, the research examined the connection between the adoption of the extended audit report and the relevance of accounting information and external auditing quality. Method: A purposive sample of 248 observations during a period of four years, 2016-2019 was sampled to analyze this relationship in a scientific and accurate manner. The sample in the study was confined to the companies, which apply the extended audit report, which they complete under the control of the central body or follow the system of the doubling entries.  Results:  The research has found substantial findings that indicate that the higher the degree of commitment to adopt the extended audit report, the better the relevance of the accounting information, especially in the abnormal returns of the shares. The research also established that adoption of extended audit report helps in improving quality of external auditing since auditors are guided by giving more detailed opinion that encompasses different aspects of the company.  Novelty: These findings underscore the need to use these reports to enhance the efficiency of the accounting and auditing system and hence enhance increased transparency and credibility in financial reporting.